International Court of Justice Judgments on the Protection of Individual Rights in the Context of Diplomatic and Consular Rights - Cüneyt Yüksel; Deniz Baran (Ceza Hukuku ve Kriminoloji Dergisi)
The International Court of Justice (ICJ), the main judicial body of the United Nations, has contributed significantly to the protection of human rights in its efforts to build up the rule of law on a global scale. The ICJ has dealt with issues directly related to the rights and interests of individuals in cases brought before it, and in the 21st century, began to endorse a more active approach in the protection of individual rights. This is apparent in several judgments since the early 2000s on the protection of certain consular rights. The relevant cases are LaGrand, Avena and Others, and Jadhav, the latter being one of the most recent judgments of the ICJ. In this article, these cases are examined in detail, to illustrate the abovementioned tendency of the ICJ. In particular, the different and more progressive aspects of the Jadhav Judgment compared to the LaGrand and Avena Judgments are highlighted. The main aim of this article is to prove the evolving approach of the ICJ in terms of actively protecting individual rights, through a comparison of three similar cases where it dealt with the violation of the same individual rights.